Biomimetic approaches for biomaterials development - Mano, João F. (Weinheim : Wiley-VCH Verlag GmbH & Co. KGaA, 2012)
"The book comprehensively covers biomimetic approaches to the development of biomaterials, including: an overview of naturally occurring or nature inspired biomaterials; an in-depth treatment of the surface aspects pivotal for the functionality; synthesis and self-assembly methods to prepare devices to be used in mineralized tissues such as bone and teeth; and preparation of biomaterials for the controlled/sustained release of bioactive agents. The last part reviews the applications of bioinspired materials and principles of design in regenerative medicine such as in-situ grown bone or cartilage as well as the biomimetic techniques for soft tissue engineering. The comprehensive scope of this book makes it a must-have addition to the bookshelf of everyone in the fields of Materials Science/Engineering, Nanotechnologies / Nanosciences, Medical Sciences, Biochemistry, Polymer Chemistry, and Biomedical Engineering."--
Examples of natural and nature-inspired materials. Biomaterials from marine-origin biopolymers / Tiago H Silva, Ana R C Duarte, Joana Moreira-Silva, João F Mano, Rui L Reis -- Hydrogels from protein engineering / Midori Greenwood-Goodwin, Sarah C Heilshorn -- Collagen-based biomaterials for regenerative medicine / Christophe Helary, Abhay Pandit -- Silk-based biomaterials / Silvia Gomes, Isabel B Leonor, João F Mano, Rui L Reis, David L Kaplan -- Elastin-like macromolecules / Rui R Costa, Laura Martin, João F Mano, Jose C Rodriguez-Cabello -- Biomimetic molecular recognition elements for chemical sensing / Justyn Jaworski -- Surface aspects. Biology lessons for engineering surfaces for controlling cell-material adhesion / Ted T Lee, Andres J Garcia -- Fibronectin fibrillogenesis at the cell-material interface / Marco Cantini, Patricia Rico, Manuel Salmeron-Sanchez -- Nanoscale control of cell behavior on biointerfaces / E Ada Cavalcanti-Adam, Dimitris Missirlis -- Surfaces with extreme wettability ranges for biomedical applications / Wenlong Song, Natalia M Alves, João F Mano -- Bio-inspired reversible adhesives for dry and wet conditions / Aranzazu del Campo, Juan Pedro Fernandez-Blazquez -- Lessons from sea organisms to produce new biomedical adhesives / Elise Hennebert, Pierre Becker, Patrick Flammang -- Hard and mineralized systems. Interfacial forces and interfaces in hard biomaterial mechanics / Devendra K Dubey, Vikas Tomar -- Nacre-inspired biomaterials / Gisela M Luz, João F Mano -- Surfaces inducing biomineralization / Natalia M Alves, Isabel B Leonor, Helena S Azevedo, Rui L Reis, João F Mano -- Bioactive nanocomposites containing silicate phases for bone replacement and regeneration / Melek Erol, Jasmin Hum, Aldo R Boccaccini -- Systems for the delivery of bioactive agents. Biomimetic nanostructured apatitic matrices for drug delivery / Norberto Roveri, Michele Iafisco -- Nanostructures and nanostructured networks for smart drug delivery / Carmen Alvarez-Lorenzo, Ana M Puga, Angel Concheiro -- Progress in dendrimer-based nanocarriers / Joaquim M Oliveira, João F Mano, Rui L Reis -- Lessons from nature in regenerative medicine. Tissue analogs by the assembly of engineered hydrogel blocks / Shilpa Sant, Daniela F Coutinho, Nasser Sadr, Rui L Reis, Ali Khademhosseini -- Injectable -forming scaffolds for tissue engineering / Da Yeon Kim, Jae Ho Kim, Byoung Hyun Min, Moon Suk Kim -- Biomimetic hydrogels for regenerative medicine / Iris Mironi-Harpaz, Olga Kossover, Eran Ivanir, Dror Seliktar -- Bio-inspired 3d environments for cartilage engineering / Jose Luis Gomez Ribelles -- Soft constructs for skin tissue engineering / Simone S Silva, João F Mano, Rui L Reis.
Includes bibliographical references and index.
Online resource; title from digital title page (ebrary, viewed on November 3, 2014).
Keywords: Biomedical materials; Biomimetic materials; Biocompatible Materials; Biomimetics -- methods; Tissue Engineering; MEDICAL -- Allied Health Services -- Medical Technology; MEDICAL -- Biotechnology; MEDICAL -- Family & General Practice; MEDICAL -- Lasers in Medicine; TECHNOLOGY & ENGINEERING -- Biomedical; Biomedical materials; Biomimetic materials; Electronic books